Vehicle speed control using road bumps: part 1 (2004)
"Road bumps play a crucial role in enforcing speed limits, thereby preventing overspeeding of vehicles. It significantly contributes to the overall road safety objective through the prevention of accidents that lead to deaths of pedestrians and damage of vehicles. Despite the importance of road bumps, very little research has been done to investigate into their design. While documentation exists on quantitative descriptions of road bumps, they offer little guidance to decision making. This work presents a unique approach to solving road bumps design problems. The results of our study reveal three important road bumps variables that influence the control of vehicle speeds. The key variables are bump height, bump width, and effective distance between two consecutive road bumps. Since vehicle speed control is the ultimate aim of this study the relationship between vehicle speed and other variables earlier mentioned is established. Vehicle speed is defined as the product of frequency at which a vehicle is moving over road bumps and the sum of effective distance between two consecutive road bumps. In the determination of bump height we assume a conical shaped curve for analysis as a matter of research strategy. Based on this, two stages of motion were analysed The first concerns the motion over the bump itself while the second relates to the motion between two consecutive road bumps. Fourier series was then used to formulate a holistic equation that combines these two stages. used trigonometric functions to model the behaviour of the first stage while with the second stage giving a functional value of zero since no changes in height are observed. We carried out vibration analysis to determine the effect of road bumps on a vehicular system. Arising from this a model component is referred to as an isolation factor. This offers guidance to the safe frequency at which vehicles could travel over road bumps. The work appears to contribute to knowledge in road bump research through the development of a novel approach to the control of vehicle speeds. Significant research progress could be made if engineering and academic communities at large appreciate our viewpoints. With this work it is apparent that varying of the assumptions made in terms of bump shape may produce high proliferation of beneficial research studies. Although this work may reveal a new way of investigation into road bump research, no claim is made for the work comprehensiveness. We expect experts to challenge some of our thoughts and ideas presented in this work "